Virtual chromoendoscopy for the real-time assessment of colorectal polyps in vivo: a systematic review and economic evaluation - Joanna Picot; Micah Rose; Keith Cooper; Karen Pickett; Joanne Lord; Petra Harris; Sophie Whyte; Dankmar Böhning; Jonathan Shepherd (Health Technology Assessment, 2017)
Background: Current clinical practice is to remove a colorectal polyp detected during colonoscopy and determine whether it is an adenoma or hyperplastic by histopathology. Identifying adenomas is important because they may eventually become cancerous if untreated, whereas hyperplastic polyps do not usually develop into cancer, and a surveillance interval is set based on the number and size of adenomas found. Virtual chromoendoscopy (VCE) (an electronic endoscopic imaging technique) could be used by the endoscopist under strictly controlled conditions for real-time optical diagnosis of diminutive (≤ 5 mm) colorectal polyps to replace histopathological diagnosis. Objective: To assess the clinical effectiveness and cost-effectiveness of the VCE technologies narrow-band imaging (NBI), flexible spectral imaging colour enhancement (FICE) and i-scan for the characterisation and management of diminutive (≤ 5 mm) colorectal polyps using high-definition (HD) systems without magnification. Design: Systematic review and economic analysis. Participants: People undergoing colonoscopy for screening or surveillance or to investigate symptoms suggestive of colorectal cancer. Interventions: NBI, FICE and i-scan. Main outcome measures: Diagnostic accuracy, recommended surveillance intervals, health-related quality of life (HRQoL), adverse effects, incidence of colorectal cancer, mortality and cost-effectiveness of VCE compared with histopathology. Data sources: Electronic bibliographic databases including MEDLINE, EMBASE, The Cochrane Library and Database of Abstracts of Reviews of Effects were searched for published English-language studies from inception to June 2016. Bibliographies of related papers, systematic reviews and company information were screened and experts were contacted to identify additional evidence. Review methods: Systematic reviews of test accuracy and economic evaluations were undertaken in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Meta-analyses were conducted, where possible, to inform the independent economic model. A cost–utility decision-analytic model was developed to estimate the cost-effectiveness of VCE compared with histopathology. The model used a decision tree for patients undergoing endoscopy, combined with estimates of long-term outcomes (e.g. incidence of colorectal cancer and subsequent morbidity and mortality) derived from University of Sheffield School of Health and Related Research’s bowel cancer screening model. The model took a NHS perspective, with costs and benefits discounted at 3.5% over a lifetime horizon. There were limitations in the data on the distribution of adenomas across risk categories and recurrence rates post polypectomy. Results: Thirty test accuracy studies were included: 24 for NBI, five for i-scan and three for FICE (two studies assessed two interventions). Polyp assessments made with high confidence were associated with higher sensitivity and endoscopists experienced in VCE achieved better results than those without experience. Two economic evaluations were included. NBI, i-scan and FICE are cost-saving strategies compared with histopathology and the number of quality-adjusted life-years gained was similar for histopathology and VCE. The correct surveillance interval would be given to 95% of patients with NBI, 94% of patients with FICE and 97% of patients with i-scan. Limitations: Limited evidence was available for i-scan and FICE and there was heterogeneity among the NBI studies. There is a lack of data on longer-term health outcomes of patients undergoing VCE for assessment of diminutive colorectal polyps. Conclusions: VCE technologies, using HD systems without magnification, could potentially be used for the real-time assessment of diminutive colorectal polyps, if endoscopists have adequate experience and training. Future work: Future research priorities include head-to-head randomised controlled trials of all three VCE technologies; more research on the diagnostic accuracy of FICE and i-scan (when used without magnification); further studies evaluating the impact of endoscopist experience and training on outcomes; studies measuring adverse effects, HRQoL and anxiety; and longitudinal data on colorectal cancer incidence, HRQoL and mortality. Study registration: This study is registered as PROSPERO CRD42016037767. Funding: The National Institute for Health Research Health Technology Assessment programme.